The Pathways out of Poverty in Rural Indonesia: an empirical assessment - Peter Timmer; Julian Weisbrod; Neil McCulloch (Verein für Socialpolitik, Ausschuss für Entwicklungsländer, 2006)
Since most poor live in rural areas, primarily engaged in low productivity farm activity, the pathway out of poverty must be strongly connected to productivity increases, whether they are realised in farming, rural non-farm enterprises or via urban migration. By utilizing the IFLS panel dataset for 1993 and 2000 from Indonesia, this paper shows, using empirical techniques, which pathways out of poverty were most successful in Indonesia?s past. Our findings suggest that the increased engagement of rural farmers in rural non-farm enterprises is a key way to alleviate rural poverty.
Keywords: 330